DA’WAH HYBRID: MANAGEMENT AND RESPONSE OF SURAU CONGREGATION TO THE BLENDED DA’WAH PROGRAM - Heriansyah Heriansyah; Mursyid Z. Achmad (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
ABSTRACT This research explores how the urban Muslim community, particularly the administrators of the Surau Al-Mukhlisin [a place of worship for Muslim usually smaller than a mosque] in Kubu Raya, has adapted to the latest technological advances. The administrators have integrated digital technology into their functions, including adopting a blended approach to da’wah. While conventional, in-person da’wah at the Surau continues, preserving its traditional role, they also conduct da’wah sessions through online platforms. This reflects the dual identity of urban Muslims at Surau Al-Mukhlisin: they maintain religious symbols in public spaces while embracing modern technology in their daily lives. The study aims to investigate three main areas: first, how the Surau manages and how the congregation responds to the Blended Da’wah Program; second, the obstacles encountered during its implementation; and third, the solutions adopted to overcome these obstacles. A qualitative approach was used, employing in-depth interviews and participatory observation. The informants included the administrators and active congregation members of Surau Al-Mukhlisin. The data were analyzed using thematic analysis techniques. The findings reveal that the congregation responded positively to the Blended Da’wah Program, appreciating the accessibility to religious knowledge despite their busy schedules and time constraints. They continue to value traditional, face-to-face da’wah but also seek to stay current with technological advancements. The online program includes a fiqh study every Tuesday evening, while the offline and streaming program features the Shubuh Meraih Berkah study and a monthly breakfast event. However, some obstacles include limited access to technology for some members, difficulties in adapting to new technologies, and a preference for face-to-face interactions without intermediaries. Solutions to these challenges include guiding members on how to access and navigate online meeting platforms, explaining the process of downloading and using applications like Zoom, and providing hands-on practice for those unfamiliar with online applications. Keywords: Hybrid Da’wah, Management, Response, Surau Congregation